2017
DOI: 10.1039/c7nr01582h
|View full text |Cite
|
Sign up to set email alerts
|

Diruthenium(ii,iii) metallodrugs of ibuprofen and naproxen encapsulated in intravenously injectable polymer–lipid nanoparticles exhibit enhanced activity against breast and prostate cancer cells

Abstract: A unique class of diruthenium(ii,iii) metallodrugs containing non-steroidal anti-inflammatory drug (NSAID), Ru(NSAID), have been reported to show anticancer activity in glioma models in vitro and in vivo. This work reports the encapsulation of the lead metallodrug of ibuprofen (HIbp), [Ru(Ibp)Cl] or RuIbp, and also of the new analogue of naproxen (HNpx), [Ru(Npx)Cl] or RuNpx, in novel intravenously (i.v.) injectable solid polymer-lipid nanoparticles (SPLNs). A rationally selected composition of lipids/polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Whereas examples of ruthenium complexes bearing ligands that have a specific target in hormone receptor positive breast cancers are limited, several complexes bearing other types of bioactive ligands with different targets were also found to display a considerable activity for hormone receptor positive cancers. For example, several reports have demonstrated that nonsteroidal anti-inflammatory drugs (NSAIDs) have promising anticancer properties, making them suitable ligands for the design of multifunctional anticancer ruthenium complexes [75][76][77]. The main mode of action of NSAIDs in different cancer types, including breast cancer, is believed to be associated with the inhibition of the cyclooxygenase (COX) enzyme [75,78].…”
Section: Other Ruthenium Complexes For the Treatment Of Hormone Recepmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas examples of ruthenium complexes bearing ligands that have a specific target in hormone receptor positive breast cancers are limited, several complexes bearing other types of bioactive ligands with different targets were also found to display a considerable activity for hormone receptor positive cancers. For example, several reports have demonstrated that nonsteroidal anti-inflammatory drugs (NSAIDs) have promising anticancer properties, making them suitable ligands for the design of multifunctional anticancer ruthenium complexes [75][76][77]. The main mode of action of NSAIDs in different cancer types, including breast cancer, is believed to be associated with the inhibition of the cyclooxygenase (COX) enzyme [75,78].…”
Section: Other Ruthenium Complexes For the Treatment Of Hormone Recepmentioning
confidence: 99%
“…It is noteworthy that NSAIDs may not only induce an anticancer activity in hormone receptor positive breast cancers, but also in TNBC, making them versatile moieties for the design of ruthenium species for breast cancer treatment. de Oliveira Silva et al (2017) reported diruthenium(II,III) metallodrugs, (16) (Figure 4), of ibuprofen (Ru-Ibp) and naproxen (Ru-Npx) encapsulated into intravenously injectable solid-polymer-lipid nanoparticles (Ru-NSAID-SPLNs), which were prepared from a combination of two lipids (myristic acid and ethyl arachidate ester) [77]. The in vitro cytotoxicity of both dimeric metallodrugs was first studied in a triple negative breast cancer cell line, MDA-MB-231, and compared with that of ibuprofen and naproxen alone, and that of a ruthenium complex used as a control (which does not contain any bioactive ligand, [Ru 2 (O 2 CCH 3 ) 4 Cl]).…”
Section: Ruthenium Complexes Bearing Nonsteroidal Anti-inflammatory Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Alves Rico et al reported diruthenium (II,III) metallodrugs of ibuprofen and naproxen encapsulated into intravenously injectable solid–polymer–lipid nanoparticles to show anticancer activity in glioma models in vitro and in vivo. [ 59 ] Higher cytotoxicity was observed for the Ru‐complexes compared with the separate ligands, suggesting a contribution from the metal in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…Since mid-1960’s when Stephenson and Wilkinson [1] described the synthesis of the first mixed-valent [Ru 2 Cl(O 2 CR) 4 ] (R = alkyl) compound and Cotton and col [2] the first crystal structure, a big number of Ru 2 5+ paddlewheel diruthenium complexes with Ru-Ru bond order of 2.5 have been synthesized and characterized [3] , [4] , [5] , [6] , [7] , [8] . These compounds have attracted interest for their practical applications in catalysts [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , biomedicine [17] , [18] , [19] , [20] , biotechnology [21] , [22] , [23] , [24] , [25] , [26] or by their potential in material science due to their unique magnetic [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] and redox properties [37] .…”
Section: Introductionmentioning
confidence: 99%